An "imaging-biopsy" strategy for colorectal tumor reconfirmation by multipurpose paramagnetic quantum dots. (April 2015) - Xing, Xiaohong; Zhang, Bingbo; Wang, Xiaohui; Liu, Fengjun; Shi, Donglu; Cheng, Yingsheng
Abstract: Glucose transporter1 (Glut1) plays important roles in treatment of colorectal cancer (CRC) involving early-stage diagnosis, subtype, TNM stage, and therapeutic schedule. Currently, in situ marking and tracking of the tumor biomarkers via clinical imaging remains great challenges in early stage CRC diagnosis. In this study, we have developed a unique cell-targeted, paramagnetic-fluorescent double-signal molecular nanoprobe for CRC in vivo magnetic resonance imaging (MRI) diagnosis and subsequent biopsy. The unique molecular nanoprobe is composed of a fluorescent quantum dot (QD) core; a coating layer of paramagnetic DTPA-Gd coupled BSA ( Gd DTPA∙BSA), and a surface targeting moiety of anti-Glut1 polyclonal antibody. The engineered Gd DTPA∙BSA@QDs-PcAb is 35 nm in diameter and colloidally stable under both basic and acidic conditions. It exhibits strong fluorescent intensities and high relaxivity (r1 and r2 : 16.561 and 27.702 s −1 per mM of Gd 3+ ). Distribution and expression of Glut1 of CRC cells are investigated by in vitro cellular confocal fluorescent imaging and MR scanning upon treating with the Gd DTPA∙BSA@QDs-PcAb nanoprobes. In vivo MRI shows real-time imaging of CRC tumor on nude mice after intravenously injection of the Gd DTPA∙BSA@QDs-PcAb nanoprobes. Ex vivo biopsy is subsequently conducted for expression of Glut1 on tumor tissues. These nanoprobes are found biocompatible in vitro and in vivo . Gd DTPA∙BSA@QDs-PcAb targeted nanoprobe is shown to be a promising agent for CRC cancer in vivo MRI diagnosis and ex vivo biopsy analysis. The "imaging-biopsy" is a viable strategy for tumor reconfirmation with improved diagnostic accuracy and biopsy in personalized treatment.